The genius loci of crime: revealing associations in time and space - Ratcliffe, Jeremy H. (1999)
In most police services the only spatial and temporal analysis of crime was conducted until recently by statisticians at the force headquarters, with little or no regard for any short term or localised patterns of crime. In recent years there has been a move towards a more decentralised, proactive style of British policing focused at the police divisional and community level. This has left an intelligence void where force level analysis techniques are neither appropriate nor subtle enough to elicit any meaningful information at a local level from the mass of crime data generated within the police service.